Eco Friendly Synthesis, Characterization and Antibacterial Activity of ZnO Nan particles using Bacillus Subtilis against Multi-Drug Resistant Bacteria - Ayad F. Alkaim (Journal of Global Pharma Technology, 2017)
Zinc oxide nanoparticles have received likely attention due to their immense uses. For such purpose, the improvement of innovative and biological methods is in significant request for raising these materials in industrial field. This document describes a unique way for the biosynthesis of ZnO nanoparticles using abacillus subtilis. The morphology structure and stability of the synthesized ZnO nanoparticles were studied using XRD, FTIR, FE-SEM and TEM. The results showed that the synthesized nanoparticles are stable, hexagonal phase, spherical with extreme particles in size range within 7–19 nm in diameter and has antibacterial activity against MDR bacteria from different sources.Keywords: Eco friendly Synthesis.